MINIMAL CHANGE DISEASE, THE LEADING CAUSE OF GLOMERULOPATHIES IN PAEDIATRIC POPULATION AT PESHAWAR - Khan, Ahmad Zeb; Ahmad, Aziz (Journal of Ayub Medical College Abbottabad, 2010)
Background: Glomerulonephritis (GN) is a relatively rare disease with numerous subtypes. Most regional nephrology centres see only a limitednumber of patients with each type of GN every year. The objective of this study was to find out the pattern of glomerulopathies in paediatric population, undergoing renal biopsy in Peshawar. Methods: This was a prospective study carried out at the Department of Nephrology, Khyber Teaching Hospital, Peshawar from May 2002 to May 2004. Ultrasound guided percutanous renal biopsies were carried out in patients with the findings of: 1) Nephrotic range proteinuria in children, 2) Non-nephrotic range proteinuria with evidence of hypertension/haematuria/deranged renal function or active sediments on urine microscopy, 3) Steroid resistant nephrotic syndrome in children, and 4) Children with nephrotic syndrome who were not tolerant of steroid therapy or were considered for immunosuppressive drugs. Results: A total of 155 renal biopsies were taken. Out of these 90 were male patients and 65 were female. The most common histopathological lesion among children population was Minimal Change Disease (42.66%) followed by Focal Segmental Glomerulosclerosis (25.33%) and Membranous Glomerulonephritis (16.0%). Nephrotic range proteinuria was most prevalent in Minimal Change Disease and Membranous Glomerulonephritis followed by Focal Segmental Glomerulosclerosis. Non-nephrotic range proteinuria was mostly seen in patients with Membranoprolifirative Glomerulonephritis. Conclusion: In paediatric population, Minimal Change Disease is the most commonly encountered glomerulopathy, followed by Focal Segmental Glomerulosclerosis and Membranous Glomerulonephritis. Keywords: Nephrotic Syndrome, Renal biopsy, Proteinuria, Glomerulopathy